Modeling land use dynamics in Borkena watershed, Awash River basin, Ethiopia: Implications for sustainable land management - Engdaye Mersha; Sileshi Degefa; Mekuria Argaw; Wondimagegn Mengist (Sustainable Environment, 2024)
The land use and land cover (LULC) change has far-reaching repercussions on both natural ecosystems and socioeconomic systems worldwide. The objective of this study is to investigate the dynamics of LULC, identify its causes, and evaluate its magnitude over three distinct time intervals (1993–2003, 2003–2013, and 2013–2023) in the Borkena watershed. Various methodologies, including remote sensing techniques, field observations, and focus group discussions, were employed to analyze the changes in LULC. Additionally, community perceptions were assessed through Focus Group Discussions (FGDs) and Key Informants Interviews (KIIs). Four LULC classification maps were generated and utilized to analyze land use changes, while image classification was conducted using the maximum likelihood method. The six primary land use and land cover categories considered were forest, cultivated land, shrubland, water bodies, built-up areas, and bare land. The results indicated an increase in settlements (77%), cultivated land (12%), and bare land (7%) between 1993 and 2023, while a decrease in forest cover (10%), shrubland (150%), and water bodies (−101%). These changes were predominantly observed in areas with gentle slopes (0–8%) and low altitudes (0–500 m). The findings suggest a significant expansion of agricultural and urbanization activities within the watershed. Anthropogenic activities such as agriculture and settlement had a more pronounced impact on low-lying and gently sloping areas compared to high-altitude and steep slope regions. Key informants and focus group discussions highlighted rapid population growth, rainfall variability, soil fertility decline, and a scarcity of fuelwood as the primary factors contributing to these changes.